Junctional Adhesion Molecules: Potential Proteins in Atherosclerosis - Wang, Junqi; Chen, Xiaoping (Frontiers in Cardiovascular Medicine, 2022)
Junctional adhesion molecules (JAMs) are cell-cell adhesion molecules of the immunoglobulin superfamily and are involved in the regulation of diverse atherosclerosis-related processes such as endothelial barrier maintenance, leucocytes transendothelial migration, and angiogenesis. To combine and further broaden related results, this review concluded the recent progress in the roles of JAMs and predicted future studies of JAMs in the development of atherosclerosis.